Effect of distance tip gap on screw electrode of ozone generator: simulation and experimental study - Djulil Amri; Syarifa Fitria; Muhammad Irfan Jambak; Rizda Fitri Kurnia; Dwirina Yuniarti; Zainuddin Nawawi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
Ozone generation using screw-type electrodes with different distance peak to peak was studied, with the view to comparing the effectiveness of the two technologies in improving for high ozone concentration. Current density, heat flux, and distribution electric potential were performed by using simulation software Ansys. These simulations indicate that the screw-type electrode with a distance of 2 mm generates the higher current density, the result is the same as the initial assumption that the screw distance 2 mm will be better than distance 1.5 mm because it has lower heat flux. Experimental work confirms that a screw model with a distance of 2 mm also has high ozone concentration than a distance 1.5 mm screw model due to current density making electric field strength also higher to produce high ozone concentration, as was also noted by previous authors.